2023
DOI: 10.3390/diagnostics13071281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Preoperative Biliary Drainage in Patients with Ductal Adenocarcinoma of the Pancreatic Head

Abstract: Our aim was to study the association between preoperative biliary drainage (PBD) and morbidity following cephalic pancreaticoduodenectomy (CPD) for pancreatic ductal adenocarcinoma (PDAC) and its prognostic impact, which is still controversial in the literature. A retrospective study was conducted, which included 128 patients who underwent CPD for PDAC, divided into two groups: those who underwent PBD (group 1) and those who did not undergo this procedure (group 2). Group 1 was subdivided according to the drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This indicates that preoperative biliary drainage does not increase the frequency of postoperative complications in PD of malignant obstructive jaundice. Amaral et al's [22] study showed that compared to the Non-PBD group, the positive rate of intraoperative bill cultures in the PBD group was notable higher. Our study shows that the positive rate of bacterial culture in postoperative drainage uid in the PBD group exceed that in the Non-PBD group (19% versus 10%, P = 0.095), but the difference is not extremely obvious.…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that preoperative biliary drainage does not increase the frequency of postoperative complications in PD of malignant obstructive jaundice. Amaral et al's [22] study showed that compared to the Non-PBD group, the positive rate of intraoperative bill cultures in the PBD group was notable higher. Our study shows that the positive rate of bacterial culture in postoperative drainage uid in the PBD group exceed that in the Non-PBD group (19% versus 10%, P = 0.095), but the difference is not extremely obvious.…”
Section: Discussionmentioning
confidence: 97%